RETINOPATHY OF PREMATURITY IN NEONATES WITH UNSTABLE CLINICAL COURSE - Narang, Gursharan Singh; Kaur, Kajaldeep; Singh, Gurmeet; Ashwani kumar (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objective: The objective of this study was to determine incidence of development of retinopathy of prematurity (ROP) in infants with GA ≥34 weeks or BW ≥1750 g having unstable clinical course. Methods: This was a cross-sectional study, all infants with GA ≥34 weeks or BW ≥1750 g having unstable clinical course were enrolled after taking informed consent from the parents. All these neonates were screened for ROP at 4 weeks of gestation age. Incidence of ROP was calculated and risk factors were also evaluated. Results: Out of total 426 admissions to neonatal intensive care unit, 52 babies satisfied the inclusion criteria and were enrolled in study. Incidence of ROP in neonates ≥34 weeks was 4%. Among the various neonatal factors, the presence of Bronchopulmonary dysplasia, administration of blood transfusions, and surfactant therapy were having significant association with ROP. Conclusion: ROP can even occur in babies with GA ≥34 weeks and normal birth weight neonates. Careful and timed retinal examination of all at risk infants will minimize the development of ROP and later on blindness which will lower the social and economic burden.